Simposio endometriosis: presentación - Ascenzo Palacio, Alberto (2026)
I would like to begin this presentation by noting that endometriosis firstdrew my attention—and subsequently became a subject of particularinterest—during my medical training. This is due to the fact that it is a disease for which neither its etiology nor its progression is fully understood. It may be entirely asymptomatic or manifest with markedly florid symptoms, and, moreover, we currently lack a definitive treatment. Insome cases, we are able to alleviate patients’ discomfort, yet we remainunable to cure the condition.